Co-Design of a Family Peacebuilding Kit: Case Study in Binar Bermain Belajar Community - Ica Ramawisari; Nurul Fitriana Bahri; Muhammad Syarif Jayeng Hendrawan; Abimanyu Fitrian Faza; Satria Budiana Tresna (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
Existing educational products for families often focus narrowly on cognitive skills or behavioral training, overlooking emotional awareness, conflict resolution, and positive communication between parents and children. Previous studies in family education and parenting typically adopt top-down design approaches, where experts create tools without systematically involving end users in the creative process. This creates a gap between product design and the real-life needs, values, and contexts of families. This research addresses that gap by applying a participatory design approach—specifically co-design—collaborating directly with the Binar Bermain Belajar parenting community in Indonesia. Using the Double Diamond design model, the study engages families throughout all design stages: Discover, Define, Develop, and Deliver. The resulting Family Peacebuilding Kit integrates interactive tools, including Peace Action Cards and Emotion Reflection Cards, to support playful yet meaningful dialogue in households. By prioritizing users as co-creators rather than passive recipients, this study contributes to the field of social design and community-based learning by demonstrating how family-centered co-design processes can produce more relevant, engaging, and sustainable educational interventions—bridging the disconnect between academic design frameworks and real-world family dynamics.